Hadron interaction simulation in atmospheric neutrino flux calculations - Barr, G (2007)
The aspects of hadron simulation affecting the calculation of unoscillated atmospheric neutrino fluxes is discussed. The method of simulating the atmospheric cascades is described. An evaluation of the errors on the atmospheric neutrino fluxes and various experimentally convenient ratios is presented. A new measurement of hadron production with the NA49 experiment at CERN is briefly reported.